(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Anemia is now globally recognized major public health problem. The present study was undertaken to investigate the prevalence of anemia and interrelationship of anemia with BMI among adult rural population of West Bengal state, India. Method: Anthropometric measures, nutritional parameters, heart rate and hemoglobin were measured from 310 adult subjects by using standard technique. Results: The prevalence of anemia was high among both sexes and more than the global prevalence. The anemic individuals consumed nutritionally deficient diet than the non-anemic individuals. The prevalence of anemia was significantly high in underweight and normal groups. The Odds ratios became significantly higher in underweight group than normal and overweight/obese groups of both sexes. Conclusions: The prevalence of anemia in the adult rural population might be related to dietary deficiency and poor dietary patterns. The present study was hypothesized that the subjects with low BMI would have a higher risk of anemia compared to normal or overweight subjects.